2019
DOI: 10.1088/1361-6463/ab34c1
|View full text |Cite
|
Sign up to set email alerts
|

Account of diffusion in local thermodynamic equilibrium and two-temperature plasma models

Abstract: A self-consistent account of the effect of diffusion on charge transport in local thermodynamic equilibrium (LTE) and two-temperature (2T) ionization-equilibrium plasmas amounts to introducing into Ohm's law, in addition to the conventional term proportional to the electric field (conduction current) and thermal-diffusion terms, also terms describing the diffusion due to plasma composition variations, which are proportional to the temperature gradient (or, in the case of 2T plasmas, to ∇T e and ∇T h ) and to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A useful improvement would be to introduce, in the framework of the 2T equations describing the arc bulk, the account of diffusion current in Ohm's law, as mentioned in section 2.2.2. Representative modelling results [49] showed that such a form of Ohm's law, when introduced into standard LTE or 2T models, may describe the electric field reversal in front of arc anodes, an effect that has been simulated previously only by means of (more complex) models taking into account deviations from ionization equilibrium.…”
Section: Approach With 2t Description Of the Arc Bulkmentioning
confidence: 99%
See 2 more Smart Citations
“…A useful improvement would be to introduce, in the framework of the 2T equations describing the arc bulk, the account of diffusion current in Ohm's law, as mentioned in section 2.2.2. Representative modelling results [49] showed that such a form of Ohm's law, when introduced into standard LTE or 2T models, may describe the electric field reversal in front of arc anodes, an effect that has been simulated previously only by means of (more complex) models taking into account deviations from ionization equilibrium.…”
Section: Approach With 2t Description Of the Arc Bulkmentioning
confidence: 99%
“…Note that Ohm's law is written in the form j = σE in works dedicated to the modelling of LTE and 2T plasmas, except for those that take into account thermal diffusion. The account of the diffusion due to variations of the plasma composition was introduced in [49], in the same way as the effect of the diffusion over the energy transport in chemical-equilibrium mixtures is routinely taken into account by means of the reactive thermal conductivity. The result was a modification of Ohm's law in LTE and 2T plasmas: new terms proportional to the temperature gradient (or, in the case of 2T plasmas, to ∇T e and ∇T h ) and to the plasma pressure gradient have appeared.…”
Section: The Arc Bulkmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15] In the second, the arc column and sheath are described separately, that is, different governing equations for local thermal equilibrium (LTE) arc column and non-local ther-mal equilibrium (non-LTE) sheath are used, which requires elaborate mesh division and large computing resources, so the requirement of solving accuracy is relatively high. [16][17][18][19] With these two modeling methods, researchers have obtained significant parameters of voltage drop, electron number density and voltage-current characteristics, [20] electron and ion number density, [21,22] and electron temperature [21,23] of the sheath. Benilov et al established a model to describe the arcsheath-electrode heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Other papers focus on measurements of the plasma to elucidate its interaction with electrodes or surrounding materials [1-3, 10, 17, 18].A review article considers the state-of-the-art and the remaining challenges in modelling arc-electrode interactions [16]. Studies are reported on cathode spot formation [7] and arc-cathode attachment [6] for non-thermionic cathodes, the change in cathode shape [4] and current-voltage characteristics [1] in thermionic arcs, metal vapour production and transport in welding arcs [2, 5], tungsten vapour transport in a high-pressure arc lamp [8], arc extinction in high power circuit breakers [11], the application of emission spectra to determine arc properties [17], and the effect of diffusion on charge transport in local thermodynamic equilibrium and two-temperature plasmas [19]. Other papers address the interaction between plasma jets and solid surfaces involving ablation-controlled arc plasma in air [9,10], chemical reactions between the plasma and the surface such as in solid propellant ignition [15], and anode erosion in DC arcs [18].Special attention is also given to plasma-particle interaction in the process of metal particle evaporation for the synthesis of nanosized metallic particles.…”
mentioning
confidence: 99%